THE EFFECT OF SCRAMBLE GAME IN LEARNING ENGLISH VOCABULARY AT MAN 1 ACEH TENGGARA ACADEMIC YEAR 2021-2022 - RICKI ADIT YAWIJAYA; SABRUN JAMIL; RAJA FAUZIAH (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The purpose of this study is two of them, the first is to determine the influence of the scramble game learning model and conventional learning on the understanding of writing vocabulary and the difference in knowing the influence of the scramble game learning model and conventional learning on the understanding of writing vocabulary at MAN 1 Aceh Tenggara in The 2021-2022 Academic Year. The method used is quantitative. The research design used is one group pretes-posttest design. The population study totaled 272 students while the research sample amounted to two classes, each class consisting of 32 students. The findings of his research can be explained that the results significance Paired Sample T-test that 0,000 (Asymp . Sig) < 0,05 then H0 rejected means there is the difference or the influence of the scramble game model on understanding write vocabulary in experiment class. Results significance Paired Sample T-test that 0,000 (Asymp . Sig) < 0,05 then H0 rejected means there is the difference or the influence of conventional models to understanding write vocabulary in the control class. Results Paired Sample T-test, that if 13,707 (t value) > 2,03011 (t table) it means hypothesis was received at experiment class. Results Paired Sample T-test, that if 13,707 (t value) > 2,03011 (t table) it means hypothesis was received at control class. Results Independent Sample T-test was obtained score significance (2-tailed) is 0.000 < 0.05, then could concluded that " there " difference in average results study student between the scramble game learning model and the conventional model ". Next, for the value of t can be concluded that 11.660 (t value) > 2.03011 (t table), which means the hypothesis was received.